Muscle stiffness of posterior lower leg in runners with a history of medial tibial stress syndrome. (3rd April 2017) - Saeki, J.; Nakamura, M.; Nakao, S.; Fujita, K.; Yanase, K.; Ichihashi, N.
Abstract : Previous history of medial tibial stress syndrome (MTSS) is a risk factor for MTSS relapse, which suggests that there might be some physical factors that are related to MTSS development in runners with a history of MTSS. The relationship between MTSS and muscle stiffness can be assessed in a cross‐sectional study that measures muscle stiffness in subjects with a history of MTSS, who do not have pain at the time of measurement, and in those without a history of MTSS. The purpose of this study was to compare the shear elastic modulus, which is an index of muscle stiffness, of all posterior lower leg muscles of subjects with a history of MTSS and those with no history and investigate which muscles could be related to MTSS. Twenty‐four male collegiate runners (age, 20.0±1.7 years; height, 172.7±4.8 cm; weight, 57.3±3.7 kg) participated in this study; 14 had a history of MTSS, and 10 did not. The shear elastic moduli of the lateral gastrocnemius, medial gastrocnemius, soleus, peroneus longus, peroneus brevis, flexor hallucis longus, flexor digitorum longus, and tibialis posterior were measured using shear wave elastography. The shear elastic moduli of the flexor digitorum longus and tibialis posterior were significantly higher in subjects with a history of MTSS than in those with no history. However, there was no significant difference in the shear elastic moduli of other muscles. The results of this study suggest that flexor digitorum longus and tibialis posterior stiffness could be related to MTSS.